Community-based adaptation to flood: a systematic literature review / Musa Mustapha Danraka, Sapura Mohamad and Siti Nur Hannah Ismail - Danraka, Musa Mustapha; Mohamad, Sapura; Ismail, Siti Nur Hannah (Universiti Teknologi MARA, Perak, 2024)
Communities have developed established knowledge and techniques to foresee, diminish the impacts of, react to, and restore from floods and comparable risks due to their intimate connections to their ecological environment. These are generally recognized as Community-based Adaptation (CBA) responses collectively. The motivation behind embarking on this systematic review stems from the fact that scholars and policymakers come across conflicting information in this field, making it challenging to handle. This review aims to comprehend the present state of knowledge on CBA to flood. The practices encompassing community-based approaches to flood management, the historical examination of these practices, and the current understanding of their alignment with flood adaptation have all been delineated via a comprehensive analysis of relevant scholarly works. This thorough investigation yielded a corpus of 25 articles written exclusively in the English language, which were subjected to both qualitative and quantitative scrutiny. The study discovered a wide range of community mobilisation strategies, with the majority of research on these focused on developed nations, ranging from early warning systems and hazard forecasts to livelihood-based adaptation. This systematic review assists in identifying new and significant study fields, the evolution of publications through time, patterns of author collaboration, and future research directions. The study identified the author with the most publications and citations, the journal with the most publications, and the most common words from the content analysis. This study provides a general overview of the topic for academics interested in CBA solutions and paves the path for additional study in this area. Thus, government programmes for general recovery following a flood can be put into action more swiftly.